Analysis Of Wasatiyyah Thoughts Of Muhammad Mahfudh Tarmadzi's On Takfirism In His Is'af Al Mathali' - Marwal, Muhammad Ilyas; Ilyas, Muhammad Fadhlirobby (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
Wasatiyyah thinking, or moderation, is an essential principle in Islamic teachings which prioritizes balance and tolerance in religious life. This concept becomes very relevant amidst the challenges of extremism and intolerance modern society faces. Muhammad Mahfudh Tarmadzi, a great Indonesian cleric, made a significant contribution through his work Is'af al-Mathali', which offers a moderate view in dealing with the phenomenon of takfirism, an ideology that disbelieves fellow Muslims. This research aims to explore Wasatiyyah Mahfudh Tarmadzi's thoughts, focusing on its application in overcoming the issue of takfirism. This research uses a text analysis methodology on Is'af al-Mathali's work to understand the application of balance, justice, and tolerance principles in responding to contemporary religious issues, especially takfirism. Mahfudh Tarmadzi strongly criticized the practice of takfirism, emphasizing the importance of solid evidence and a fair process in accusing infidels because takfirism often triggers conflict and violence among Muslims. The main aim of this research is to emphasize the relevance of Wasatiyyah Mahfudh Tarmadzi's thoughts in facing current religious challenges, especially in countering takfirism. This research also aims to examine Mahfudh Tarmadzi's contribution to promoting a more harmonious and peaceful religious life. It is hoped that the research results will provide in-depth insight into the importance of Wasatiyyah in building a tolerant society amidst the threat of extremism and radicalism